Mapping Manajerial Kompetensi di PT. E-T-A Indonesia - Tanto, Ronny; Rahardjo, Jani (Jurnal Titra, 2014)
Managerial competencies play an important role in measuring the managersperformance. At present, PT E-T-A Indonesia has not had this kind of measurement,while the company aims to detect the differences between average and excellentmanagers. The objective of this research is to map managerial competencies in PT E-T-AIndonesia. The first step was on recording job description of each department manager.Secondly, we made the general dictionary of managerial competencies. Based on thesurvey results 6 competencies were considered as essential, namely problem solving anddecision making, leading others, holding people accountable, service orientation,coaching, and strategic thinking. Then, questionnaires on these variables was made anddistributed among managers. Method of peer assessment was used to evaluate themanagers performance, while the method is lack of objectiveness. Having the map ofmanagerial competencies PT E-T-A Indonesia be able to identify the performance ofmanagers across the company and have a road to improve the abilities and capabilitiesof their employees.